2020
DOI: 10.1016/j.ejpb.2020.05.025
|View full text |Cite
|
Sign up to set email alerts
|

Drug-eluting wound dressings having sustained release of antimicrobial compounds

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…NFs are non-toxic to human dermal fibroblasts (HDF) cells [ 102 ]. Furthermore, it has also been reported that HA-ZnO nanocomposite enhanced the cytocompatibility of essential oils [ 103 , 104 ]. After 24 h, all antibacterial NFs formulations showed excellent antibacterial activity against S. aureus .…”
Section: Ha-mnps and Wound Healing Applicationsmentioning
confidence: 99%
“…NFs are non-toxic to human dermal fibroblasts (HDF) cells [ 102 ]. Furthermore, it has also been reported that HA-ZnO nanocomposite enhanced the cytocompatibility of essential oils [ 103 , 104 ]. After 24 h, all antibacterial NFs formulations showed excellent antibacterial activity against S. aureus .…”
Section: Ha-mnps and Wound Healing Applicationsmentioning
confidence: 99%
“…Bacterial contamination of a wound might occur at any time during the wound healing process; therefore, prolonged antimicrobial agent release from the wound dressing is beneficial [ 31 ]. We believe that prolonged release of tannic acid may be beneficial to the antibacterial properties of a material.…”
Section: Discussionmentioning
confidence: 99%
“…97 Combining antibiotics with other methods such as adequate nutrition, proper dressing, and elimination of dead tissues can reduce the exogenous microbial infection. 98 However, the unnecessary exposure of the resident microflora to excessive antibiotics can lead to the formation of antibioticresistant strains. 99 Moreover, the antibiotic effect on pre-existing normal bacterial flora is difficult to control.…”
Section: Chemical Drugsmentioning
confidence: 99%
“…Topical application provides high and sustained concentrations of antibiotics to the wound site, which requires a low quantity of drugs compared with systemic therapy 97 . Combining antibiotics with other methods such as adequate nutrition, proper dressing, and elimination of dead tissues can reduce the exogenous microbial infection 98 . However, the unnecessary exposure of the resident microflora to excessive antibiotics can lead to the formation of antibiotic‐resistant strains 99 .…”
Section: Bioactive Moleculesmentioning
confidence: 99%